The Adoption and Implementation of the International Public Sector Accounting Standards: The challenges faced by the United Nation in producing UN-IPSAS compliant financial reports in Kenya. - Whitefield, Aleg A.; Savvas, Panayiotis (International Journal of Finance and Accounting, 2016)
Purpose:The purpose of this study was to assess the challenges faced by United Nations, Nairobi in adopting and implementing IPSAS. Methodology:The study used a mixed research design involving both descriptive and explanatory research designs to describe the state of affairs of the study variables as well as test the cause and effect relationships between variablesAccording to United Nations (UN) website, there are 13 United Nations agencies in Nairobi Kenya with a total of 540 accountants. The choice of accountants as a population is because they are the most knowledgeable users. The study units for this study werethe junior and senior accountants.The sampling units for the study were drawn from the 13 agencies in the UN team of Kenya. A sample size of 20% of the population was taken as the sample size. This yielded 108 accountants. Random sampling was done. A close ended questionnaire based on a likert scale was used to collect data. Data wasanalyzed by use of descriptive and inferential statistics. Specifically, frequencies count and regression analysis results were generated using SPSS version 20. Results:The study concluded that; technological challenges, organization challenges, financial challenges and perceived usefulness challenges significantly influence the rate of IPSAS adoption by UN agencies. Unique contribution to theory, practice and policy:The study recommended that practitioners in the field of financial management and IPSAS software development should address the technological challenges associated with the adoption of IPSAS accounting. In particular, technical support from trained accountants, adequate ICT infrastructure and provision of training manuals would improve IPSAs adoption.